Study of interference localization using single satellite based on signal strength distribution in multi-beam antenna for satellite communications system. (May 2018) - He, Chao; Xie, Zhi-dong; Bian, Dong-ming; Zhong, Xi-jian
Large onboard antennas with multi-beams are used almost in all the Geostationary Earth Orbit satellite communications systems, which are always disturbed by jams and inferences. However, there are lots of factors restricting interference localization in satellite communications system because the system is not designed for location-oriented. This article makes use of the characteristic that each spot beam of multi-beams antenna has different gain at the position of interference, establishes the localization equations set by using the ground projection model of multi-beams antenna pattern, and gives two methods of solving equations. Thus, it proposes interference localization algorithm using single satellite, based on antenna gain and the distribution of signal strength in multi-beam space. Because of not depending on extra onboard equipments and other facilities, it has no effect on the construction and operation of satellite communications system. From the results of analyses and simulations, the localization precision can satisfy the general practical requirement. The algorithm could be used in checking the interference of the system, decision supporting of anti-jamming, and improving operation and management of the system.